A new chronology for Rhafas, Northeast Morocco, Spanning the North African Middle Stone Age through to the Neolithic - Doerschner, N; Fitzsimmons, K; Ditchfield, P; McLaren, S; Steele, T; Zielhofer, C; McPherron, S; Bouzouggar, A; Hublin, J (Public Library of Science, 2016)
Archaeological sites in northern Africa provide a rich record of increasing importance for the origins of modern human behaviour and for understanding human dispersal out of Africa. However, the timing and nature of Palaeolithic human behaviour and dispersal across north-western Africa (the Maghreb), and their relationship to local environmental conditions, remain poorly understood. The cave of Rhafas (northeast Morocco) provides valuable chronological information about cultural changes in the Maghreb during the Palaeolithic due to its long stratified archaeological sequence comprising Middle Stone Age (MSA), Later Stone Age (LSA) and Neolithic occupation layers. In this study, we apply optically stimulated luminescence (OSL) dating on sand-sized quartz grains to the cave deposits of Rhafas, as well as to a recently excavated section on the terrace in front of the cave entrance. We hereby provide a revised chronostratigraphy for the archaeological sequence at the site. We combine these results with geological and sedimentological multi-proxy investigations to gain insights into site formation processes and the palaeoenvironmental record of the region. The older sedimentological units at Rhafas were deposited between 135 ka and 57 ka (MIS 6 – MIS 3) and are associated with the MSA technocomplex. Tanged pieces start to occur in the archaeological layers around 109 ka, which is consistent with previously published chronological data from the Maghreb. A well indurated duricrust indicates favourable climatic conditions for the pedogenic cementation by carbonates of sediment layers at the site after 57 ka. Overlying deposits attributed to the LSA technocomplex yield ages of ~21 ka and ~15 ka, corresponding to the last glacial period, and fall well within the previously established occupation phase in the Maghreb. The last occupation phase at Rhafas took place during the Neolithic and is dated to ~7.8 ka. 39